E-commerce amidst the pandemic online consumer buying behavior towards essential goods during COVID-19 - Navarrosa, Juniel Sumayod; Rueda, Jo Vei Kirstie Leonido; Suarez, Jo Arita Goltiano; Dacuyan, Flordeliz B. (2022)
The COVID-19 pandemic has caused much distress to global economies, leading to economic shocks and the disruption of the functioning of societies. Ultimately, this accelerated the shift towards the rising e-commerce consumer culture. This study examines the online buying behavior of consumers towards essential goods amidst COVID-19, its underlying changes and factors, and the prevalent online consumer behavior of Tacloban City residents during COVID-19, from the perspectives of consumers, as the pandemic remains present in the Philippines. A quantitative approach was employed with a descriptive design. The data was obtained through simple random sampling wherein the researchers utilized an online survey. The study garnered a total of 384 respondents who are of legal age, residents of Tacloban City and have purchased essential goods online during the pandemic. Results of the study show that the demand for essential goods during the pandemic is higher than for non-essential goods as consumers facilitated their demands in purchasing other product categories and potentially centralizing on their needs and priorities during the health crisis. Factors like consumer preferences and attitudes towards online shopping during the pandemic and COVID-19 knowledge significantly influence consumers' purchasing decisions and the prevalent online consumer behaviors. Panic buying and stockpiling & hoarding were the prevalent online shopping behaviors of the study. Both convenience and recreational orientations of purchasing products online were also present. Furthermore, consumers may become occasional online shoppers for essential goods after the pandemic and will recommend such activities to other individuals but will eventually return to traditional methods of shopping in post-crisis situations.
Undergraduate thesis (B. S. in Management) -- University of the Philippines, Tacloban.